Nano-scale dendrites within the conventional dendritic arm - Xiaoping Ma (Elsevier, 2021)
The microstructures and segregations during solidification have been widely recognized in the past researches. The dendrite (termed as conventional dendrite in this paper) was recognized as the most basic entity for microstructures and microsegregation. Through careful analysis and observation in this paper, new nano-scale dendrites (with dendritic arm spacing about 500 nm) were revealed within the conventional dendritic arm (with dendritic arm spacing about 70 μm). The conventional dendrites should be recognized as macrosegregation patterns arisen in a subtle porous media. Accordingly, the research entity for microsegregation should change from the conventional dendritic arm to a more subtle entity. During solidification, temperature fluctuations with different directions, periods and intensities will superimpose to induce a dendritic temperature field on multi-scales. Because of differentiated solid fractions and liquid compositions, a dendritic macrosegregation field on multi-scales will be induced by the mass transfer. Verified by the in situ and real time observation, the subtle dendrites emerge at the later solidification stage much lower than the equilibrium eutectic temperature. Because nano-scale dendrites were recognized, new solutions were proposed for controlling macrosegregation within the conventional dendritic arm. In a more significant view, the nano-scale dendrites provide the basis for unifying the non-equilibrium solidification and the equilibrium solidification.